1994
DOI: 10.17660/actahortic.1994.356.41
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Nitrogen Source and Concentration on N Fractions in Olive Seedlings

Abstract: The effeet of!he souree (KNO" (NH')2So. and NH,NO,) and concentration (5, lO, 20 and 30 mM N) of inorganic nitro gen on total N incorporation and distribulion into different fractions (ammoniacal, ami no, amide and protein) has been determined in olive seedlings.. . Increasing concentrations of lhe nitrogen source resulted in higher total N content in tissues, e"cept for KNO, at 10 mM N. In addition, ammonium applications clearly increased !he N-amino and N-ammoniacal fractions. Incorporntion of N imo Narnide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…Between two olive cultivars, significantly more leaf area (5.90 cm 2 ) was observed in Leccino and the treatment cultivar interaction was found to be non-significant. These results are in accordance to those of Garcia et al (1994). Yet, in the present studies, the foliar applications of H 3 BO 3 and ZnSO 4 were observed to have less effect on various growth parameters.…”
Section: Resultssupporting
confidence: 93%
“…Between two olive cultivars, significantly more leaf area (5.90 cm 2 ) was observed in Leccino and the treatment cultivar interaction was found to be non-significant. These results are in accordance to those of Garcia et al (1994). Yet, in the present studies, the foliar applications of H 3 BO 3 and ZnSO 4 were observed to have less effect on various growth parameters.…”
Section: Resultssupporting
confidence: 93%
“…By means of in vitro olive zygotic embryo germination with an appropriate nitrogen supply, a reduction of the germination time, a germination percentage close to 100% and an increase of the growth rate of seedlings has been achieved (García et al, 1994;Sarmiento et al, 1994;Acebedo et al, 1997). Nevertheless, olive germinated in vitro still shows a limited proliferation rate due mainly to a lack of secondary shoot production; this technique needs further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…By in vitro culture of isolated mature olive embryos very high germination percentages have been obtained (Troncoso et al, 1991;Voyiatzis and Pritsa, 1994;Voyiatzis, 1995) in few days, even reaching 100% (Acebedo et al, 1997) and by using appropriate nitrogen forms and concentrations (García et al, 1994;Sarmiento et al, 1994) and sugar (García et al, 2002) a high in vitro growth of the seedlings was obtained. The use of a suitable substratum (Rugini, 1984), nutritive solutions (García et al, 1999) and photoperiod (Alvarado, 1994) during the hardening phase also increases the plant development.…”
Section: Introductionmentioning
confidence: 99%